2016
DOI: 10.1177/1932296816667749
|View full text |Cite
|
Sign up to set email alerts
|

Regulation Catches Up to Reality

Abstract: The FDA recently conducted an Advisory Panel meeting to evaluate the safety, efficacy, and benefits of granting a nonadjunctive label claim for the DEXCOM G5 Mobile continuous glucose monitoring (CGM) system. If approved, this claim will allow users to make day-to-day treatment decisions, including insulin dosing directly from the glucose values and rate of changes arrows generated by the CGM device, without the requirement of a confirmatory measurement with a self-monitoring blood glucose (SMBG) meter. Sporad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…Furthermore, the T1DX REPLACE BG study provided evidence of the safety and effectiveness of non‐adjunctive sensor use and registry data indicates only 26% of participants using CGM always verified the sensor glucose by performing SMBG . Practical guidelines for non‐adjunctive use are being developed . However, research and clinical experience on non‐adjunctive use of CGM systems are limited in pediatric populations …”
Section: Continuous Glucose Monitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the T1DX REPLACE BG study provided evidence of the safety and effectiveness of non‐adjunctive sensor use and registry data indicates only 26% of participants using CGM always verified the sensor glucose by performing SMBG . Practical guidelines for non‐adjunctive use are being developed . However, research and clinical experience on non‐adjunctive use of CGM systems are limited in pediatric populations …”
Section: Continuous Glucose Monitorsmentioning
confidence: 99%
“…142 Practical guidelines for non-adjunctive use are being developed. [147][148][149][150][151][152][153][154] However, research and clinical experience on non-adjunctive use of CGM systems are limited in pediatric populations. 155 4.6 | Intermittently scanned/viewed CGM Recently introduced isCGM systems are factory calibrated, small in size, light weight, have good user acceptance and satisfactory accuracy with an overall MARD of 11% to 14%.…”
Section: Accuracy Of Cgmmentioning
confidence: 99%
“…The FDA-approved simulator used in this work is a valid substitute for the preclinical testing of novel technologies in diabetes care (see, e.g., [ 43 ][ 44 ][ 45 ]). However, the use of in silico data is not meant as substitute to human trial; rather, it can be considered a good starting point for evaluating our GE method: in fact simulated data are complete, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in terms of accuracy and smart features incorporation, the Dexcom G5 Mobile CGM system is currently the leading product. With a 9% MARD, it is the first and only CGM system that can be used to make daily diabetes treatment decisions without finger pricking [57,58]. However, it still requires finger pricks for in vivo calibration, although some recent studies showed promising results towards a calibration-free scenario [59,60].…”
Section: Technological Trends and Challenges For The Next Generation mentioning
confidence: 99%